101 Fantastic Recipes for Babies, Toddlers & Children - Wardley, Bridget and Judy More (London Duncan Baird Publishers Ltd, 2006)
A collection of recipes, which aims to help your child to develop a habit of healthy eating. Featuring a symbol system giving a health profile of every dish, this book gives emphasis on practical parenting
Include Color Illustration and Index
Keywords: Children--Nutrition -- Infants--Nutrition